2013 International Conference on Computing, Networking and Communications (ICNC) 2013
DOI: 10.1109/iccnc.2013.6504261
|View full text |Cite
|
Sign up to set email alerts
|

Rate selection analysis under semi-persistent scheduling in LTE networks

Abstract: Abstract-Upcoming LTE networks have basically two different modes for scheduling data in the down-link by the base station. Dynamic scheduling brings the advantage of exploiting instantaneous channel state information while it puts on the other hand a significant burden on the system in terms of overhead and computation requirements. Especially for small packets that show up periodically, the overhead is typically too high. Therefore, the base station can serve such packet flows by the semi-persistent scheduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Therein Ei denotes the exponential integral. Equation (7) is also referred to as static SINR estimation in case RB n is persistently assigned to UE j [19]. Then, following rules of random variable transformation [20] the distribution function F Xj,n (x) and the PDF f Xj,n (x) of the random variable X j,n = Xj,n E[Xj,n] representing the scaled SINR can be calculated:…”
Section: Basic Analysis Of Pfs In Interference-limited Scenariosmentioning
confidence: 99%
“…Therein Ei denotes the exponential integral. Equation (7) is also referred to as static SINR estimation in case RB n is persistently assigned to UE j [19]. Then, following rules of random variable transformation [20] the distribution function F Xj,n (x) and the PDF f Xj,n (x) of the random variable X j,n = Xj,n E[Xj,n] representing the scaled SINR can be calculated:…”
Section: Basic Analysis Of Pfs In Interference-limited Scenariosmentioning
confidence: 99%
“…The latter is out of the scope in our analysis. In our previous publication [19] we have shown that the minimum SINR is a good approximation of EESM method. Especially, for small sets of resource blocks this approximation is plausible as the likelihood of scheduling large sets of resource blocks is relatively small.…”
Section: System Modelmentioning
confidence: 92%
“…exponential random variables with mean µ k that is uniformly distributed over a closed interval [a, b]. However, the mean SNR is known to remain constant in time for at least few seconds [25].…”
Section: A System Modelmentioning
confidence: 99%